Maternal predictors of Low Birth Weight among women attending private hospitals of Lahore, Pakistan - Saeed, Ayesha; Saeed, Amina Muhammad (Progress in Nutrition, 2017)
Background: Low Birth Weight (LBW) is a global public health concern. In Pakistan, little progress has been made towards achieving the Millennium Development Goals. The study objective was to identify maternal predictors of LBW infants among women attending private hospitals in Lahore, Pakistan. Method & Materials: A descriptive cross-sectional study was conducted at three randomly selected  tertiary care private hospitals in Lahore, Pakistan. A total of 225 participants were consecutively approached to participate in the study, 75 from each hospital. 164 gave written informed consent; the response rate was 73%. Data on demography was collected with the help of a piloted, structured questionnaire. Previous maternal anthropometric measurements, birth weight, mode of delivery, gestational age, sex and intra uterine growth retardation was obtained from patient’s file. Descriptive statistics, correlations, Anova and Chi-square was applied. A p-value of 0.05 was taken as statistically significant. Results: Inferential statistics revealed that maternal age of less than 24 years (F=4.531, p